Deforestation of seasonally dry tropical forest: a national and local analysis in Mexico - Trejo, I.; Dirzo, R.
Seasonally dry tropical forests in the neotropics reach their northernmost distribution in Mexico. This vegetation type has both a high diversity and endemism, yet information about its conservation situation is scarce. This study analyzes the loss of this forest at the national level, comparing its potential coverage with that of the early 1990s; and at the local, using a time-series of the potential vegetation and coverage in 1973 and 1989 in the state of Morelos (central Mexico). At the national level we found that only 27
Keywords: SEASONALLY DRY TROPICAL FOREST; MEXICO; DEFORESTATION; STATE OF MORELOS; LAND USE PATTERNS